Evaluation of Anticoagulation Control among Patients Taking Warfarin in University of Gondar Hospital, Northwest Ethiopia - Zelalem Liyew; Abilo Tadesse; Nebiyu Bekele; Tewodros Tsegaye (Advances in Hematology)
Introduction. Warfarin is a widely used oral anticoagulant in clinical practice. It has variable intraindividual and interindividual dose response and a narrow therapeutic index. Therefore, it requires frequent and regular international normalized ratio (INR) determination to maintain the INR within the therapeutic range. The study evaluated parameters of anticoagulation control among patients on warfarin. Methods. A cross-sectional study was conducted at University of Gondar hospital. A consecutive sampling method was used to recruit study subjects. The anticoagulation control was evaluated by determining the proportion of desired INRs and the proportion of time spent in the therapeutic range (TTR). Logistic regression analysis was used to identify associated factors with adequate TTR. A P value <0.05 was used to declare significant association. Result. A total of 338 study subjects were included in the study. The mean age of patients was 48.8 (SD = 16.4) years. Atrial fibrillation was the commonest indication for warfarin therapy. One-third (33%) of study subjects achieved the desired INRs of 2.0–3.0, while about one-tenth (13%) of patients attained good INR control (TTR ≥ 65%). Multivariate logistic regression analysis revealed no significant association of sociodemographic and clinical characteristics with good TTR outcome. Conclusion. The level of anticoagulation control with warfarin among study subjects was very low. The authors recommend to implement a validated warfarin-dose titration protocol and to establish anticoagulation clinics to mitigate the low anticoagulation level.